Multi‐echo balanced SSFP with a sequential phase‐encoding order for functional MR imaging at 7T. Issue 3 (3rd June 2022) - Liang, Huilou; Pan, Ziyi; Qian, Chencan; Liu, Chengwen; Sun, Kaibao; Weng, Dehe; An, Jing; Zhuo, Yan; Wang, Danny J. J.; Guo, Hua; Xue, Rong
Abstract : Purpose: To develop a 2D multi‐echo passband balanced SSFP (bSSFP) sequence using an echo‐train readout with a sequential phase‐encoding order (sequential multi‐echo bSSFP), and evaluate its performance in fast functional brain imaging at 7 T. Methods: As images of sequential multi‐echo bSSFP exhibit multiple ghosts due to periodic k‐space modulations, a GRAPPA‐based reconstruction method was proposed to eliminate ghosting artifacts. MRI experiments were performed to compare the image quality of multi‐echo bSSFP and conventional single‐echo bSSFP. Submillimeter‐resolution fMRI using a checkerboard visual stimulus was conducted to compare the activation characteristics of multi‐echo bSSFP, conventional single‐echo bSSFP and standard gradient‐echo EPI (GE‐EPI). Results: A higher mean structural similarity index was found between images of single‐echo bSSFP and multi‐echo bSSFP with a shorter echo train length (ETL). Multi‐echo bSSFP (ETL = 3) showed higher temporal SNR (tSNR) values than GRAPPA‐accelerated single‐echo bSSFP ( R  = 2). In submillimeter‐resolution fMRI experiments, multi‐echo bSSFP (ETL = 3) approached the imaging speed of GRAPPA‐accelerated single‐echo bSSFP ( R  = 2), but without tSNR penalty and reduced activation due to acceleration. The median t ‐value and the number of significantly activated voxels were comparable between GE‐EPI and multi‐echo bSSFP (ETL = 3) that provides virtually distortion‐free functional images and inherits the activation patterns of conventional bSSFP. Conclusion: Sequential multi‐echo bSSFP (ETL = 3) is suitable for fast fMRI with submillimeter in‐plane resolution, and offers an option to accelerate bSSFP imaging without tSNR penalty like parallel imaging.